Factor deterniman Pengetahuan Remaja Terkait Kekerasan Seksual Di Area Pendidikan - Natosba, Jum; Yulia Fitri, Eka; Ningsih, Nurma; Suwahyu, Romy; Rizona, Firnaliza (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
The phenomenon of sexual harassment is increasing and has become a serious issue in Indonesia. In daily life, many people experience this form of violence without being able to do much to avoid it and are forced to let it happen. Sexual harassment also frequently occurs in schools and on university campuses. Although students’ knowledge about sexual harassment is relatively good, it still needs to be improved. The majority of respondents have experienced at least one form of sexual harassment, including unwanted sexual attention and gender-based violence, committed by both known and unknown individuals. This study aims to explore adolescents’ knowledge of sexual harassment within educational settings. The variables explored and analyzed in this study include socio-demographic factors such as gender and age; knowledge of sexual harassment, measured using the Sexual Harassment Definition Questionnaire; experiences of sexual harassment, assessed using the Sexual Experiences Questionnaire (SEQ); and attitudes toward gender roles, measured using the Sexual Harassment Attitude Scale. Univariate, bivariate, and multivariate analyses were conducted to provide descriptive insights into the distribution of the variables examined. Most respondents had good knowledge of sexual harassment in educational environments, were under 19 years old, female, lived with their parents, and had never received information about sexual harassment within educational settings. The most dominant variable associated with knowledge of sexual harassment was age, with an OR of 2.575 (95% CI OR: 1.875–3.536), indicating that adolescents over the age of 19 were 2.575 times more likely to have lower levels of knowledge compared to those under 19 years old. When violence frequently occurs in an environment and is often witnessed, it gradually becomes normalized. Therefore, support from various stakeholders is needed to enhance adolescents’ knowledge of sexual harassment in educational settings, beginning as early as possible.